Impaired proteoglycan glycosylation, elevated TGF-β signaling, and abnormal osteoblast differentiation as the basis for bone fragility in a mouse model for gerodermia osteodysplastica - Chan, Wing Lee; Haußer-Siller, Ingrid (PLoS Genetics, 2018)
Gerodermia osteodysplastica (GO) is characterized by skin laxity and early-onset osteoporosis. GORAB, the responsible disease gene, encodes a small Golgi protein of poorly characterized function. To circumvent neonatal lethality of the GorabNull full knockout, Gorab was conditionally inactivated in mesenchymal progenitor cells (Prx1-cre), pre-osteoblasts (Runx2-cre), and late osteoblasts/osteocytes (Dmp1-cre), respectively. While in all three lines a reduction in trabecular bone density was evident, only GorabPrx1 and GorabRunx2 mutants showed dramatically thinned, porous cortical bone and spontaneous fractures. Collagen fibrils in the skin of GorabNull mutants and in bone of GorabPrx1 mutants were disorganized, which was also seen in a bone biopsy from a GO patient. Measurement of glycosaminoglycan contents revealed a reduction of dermatan sulfate levels in skin and cartilage from GorabNull mutants. In bone from GorabPrx1 mutants total glycosaminoglycan levels and the relative percentage of dermatan sulfate were both strongly diminished. Accordingly, the proteoglycans biglycan and decorin showed reduced glycanation. Also in cultured GORAB-deficient fibroblasts reduced decorin glycanation was evident. The Golgi compartment of these cells showed an accumulation of decorin, but reduced signals for dermatan sulfate. Moreover, we found elevated activation of TGF-β in GorabPrx1 bone tissue leading to enhanced downstream signalling, which was reproduced in GORAB-deficient fibroblasts. Our data suggest that the loss of Gorab primarily perturbs pre-osteoblasts. GO may be regarded as a congenital disorder of glycosylation affecting proteoglycan synthesis due to delayed transport and impaired posttranslational modification in the Golgi compartment.
Gesehen am 09.04.2019